Cyber-Physical Laboratories in Engineering and Science Education (Springer International Publishing, 2018)
This volume investigates a number of issues needed to develop a modular, effective, versatile, cost effective, pedagogically-embedded, user-friendly, and sustainable online laboratory system that can deliver its true potential in the national and global arenas. This allows individual researchers to develop their own modular systems with a level of creativity and innovation while at the same time ensuring continuing growth by separating the responsibility for creating online laboratories from the responsibility for overseeing the students who use them. The volume first introduces the reader to several system architectures that have proven successful in many online laboratory settings. The following chapters then describe real-life experiences in the area of online laboratories from both technological and educational points of view. The volume further collects experiences and evidence on the effective use of online labs in the context of a diversity of pedagogical issues. It also illustrates successful online laboratories to highlight best practices as case studies and describes the technological design strategies, implementation details, and classroom activities as well as learning from these developments. Finally the volume describes the creation and deployment of commercial products, tools and services for online laboratory development. It also provides an idea about the developments that are on the horizon to support this area.